Penilaian pelaksanaan kursus umum pengajiaan Islam di institusi pengajian tinggi swasta Malaysia / Mohd Khairi Hussin - Mohd Khairi , Hussin (2018)
Islamic Studies general course offered in private higher learning institutions in Malaysia have not been scrutinized by researchers. This study, therefore, seeks to evaluate the implementation of the aforementioned course from the perspectives of the learners. The focus of the research is to study the practice from the teaching dimension and changes in learner behaviour from the cognitive, affective and psychomotor aspects with regard to Islamic practice. The study also analyzes the effects of factors related to the dimensions of teaching, course facilities and organizational management arranged in conducting the courses. The evaluation model by Hammond (1973) has been chosen as the conceptual framework for the study. This model emphasizes the perspective of the participants or learners as being the most crucial element. Some 400 respondents were selected randomly among students of full-fledged universities from various private higher learning institutions in Peninsular Malaysia. The study utilizes the questionnaire as the main research instrument for data collection. The questionnaire is constructed in three parts; Part A is on the background of the respondents, Part B is on the teaching dimension and Part C is on the cognitive, affective and psychomotor behavior dimensions. The pilot test found the reliability of the instrument to be between .75 to .95. The findings of the study based on six main questions showed mixed results when seen from the institutional and learner behavior factors as the independent variables and the educator dimension and change in behavior as the dependent variables. The differences can be seen via the mean score and standard deviation of the level of practice in the dimensions of teaching and change in behavior from the cognitive, affective and psychomotor aspects. On the whole, the practice levels of both dimensions showed a higher-level achievement. Findings also unveiled significant differences in the cognitive, affective and psychomotor aspects of learners based on age, education level and socioeconomic status. Correlation analysis showed a close relationship between the teaching dimension and change in learner behavior. The results of variance regression-analysis showed the effects of the teaching dimension on behavior change in learners. Based on these findings, a new alternative framework theory has discovered for on-going improvement. As well as to reinforce and coordinate the offering of such courses in all institutions of higher learning of the nation in the future.